Implementasi Pengajaran Paulus Tentang Tanggung Jawab Pemimpin Kristen Berdasarkan II Timotius 2: 1-13 Di Kalangan Kepala Sekolah - Desy Prima; Hana Suparti; Paulus Sentot Purwoko (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
The purpose of this research is to find out how big is the level of implementation of the teaching of the Apostle Paul about the responsibility of Christian leaders based on II Timothy 2:1-13 among school principals in Kalam Kudus Christian schools throughout Indonesia. This research uses descriptive quantitative research, namely by using data collection techniques through the library, namely the Bible in various versions, Bible dictionaries, interpretations, Bible Encyclopedias, Interlinears, and various online and offline reading sources. The results shows that the level of implementation of the teaching of the Apostle Paul about the responsibility of Christian leaders based on II Timothy 2:1-13 among the principals of Christian Kalam Kudus Christian schools throughout Indonesia (Y) is in the medium category, this is in accordance with the hypothesis submitted.